Institut Transportasi Dan Logistik Trisakti Pemetaan Lokasi Rawan Kecelakaan Transportasi Di Ruas Jalan Tol Jakarta - Cikampek - Tamara, Ketrin Yoan (Jurnal Sistem Transportasi & Logistik, 2024)
Along with the development of transportation, demand for transportation is also increasing every year, which will indirectly increase the risk of growing traffic problems, such as accidents. According to data from PT. Jasamarga Transjawa Tol, obtained information that in the last three years there have been 525 incidents of accidents on lane A and 516 incidents of accidents on lane B. This study aims to analyze the location of accidents in accident-prone areas (black sites) on the Jakarta - Cikampek toll road by take advantage of Geographic Information Systems. It is hoped that the mapping of accident-prone areas (black sites) will serve as information as well as input to see traffic problems and also to overcome these problems for related agencies. Calling accident-prone areas (black sites) in this study uses the Z-Score statistical method. From the results of the study it was concluded that in lane A there are 13 roads which are accidentprone areas and 19 roads which are not accident-prone areas. Meanwhile, in lane B there are 14 road sections which are accident-prone areas and 18 road sections which are non-accident-prone areas during the vulnerable period from 2020 to 2022.